노인의 주관적 구강건강인식과 의치만족도 - 강용주 (Han'guk Ch'iwisaeng Hakhoe chi, 2012)
Objectives : The purpose of this study was to examine the influential factors for denture-wearing elderly people's denture satisfaction and subjective oral health and the relationship between the two in an effort to provide some information on the oral health promotion of the elderly. The subjects in this study were 192 senior citizens who were residing in the city of Busan and were wearing denture. Methods : The collected data were analyzed by the statistical package SPSS 18.0. To see whether there would be any differences in subjective oral health awareness according to general characteristics and denture-related characteristics, x2-test was carried out, and t-test or one-way ANOVA involving Duncan post-hoc analysis was utilized to look for any possible gaps in denture satisfaction according to those characteristics. Results : 1. Concerning oral health awareness by general characteristics, there were significant differences according to gender and the form of health insurance subscription. 2. As for subjective oral health awareness by denture-related characteristics, there were significant gaps according to denture-washing frequency. 3. Regarding denture satisfaction by general characteristics, there were significant differences in satisfaction with denture fixation according to living arrangements. 4. As to denture satisfaction by denture-related characteristics, there were significant differences in satisfaction with mastication and with fixation according to the type of denture. 5. Better subjective oral health awareness led to better satisfaction with mastication, better satisfaction with fixation and better aesthetic satisfaction. 6. In relation to subjective oral health awareness and denture satisfaction, that had a significant relationship to satisfaction with mastication and with fixation. Conclusions : The above-mentioned findings showed that the denture satisfaction of the denture-wearing senior citizens was linked to their subjective oral health awareness. Therefore it will be possible to improve denture- wearing elderly people's quality of life when oral health plans geared toward boosting their denture satisfaction are carried out. KCI Citation Count: 2